Wheel-like Gd42 polynuclear complexes with significant magnetocaloric effect. Issue 18 (11th April 2022) - Che, Zi-Wei; Chen, Ji-Tun; Wang, Tian-Tian; Yan, Han; Zhou, Teng-Da; Guo, Rui; Sun, Wen-Bin
Abstract : Two 42-nuclearity lanthanide complexes with a wheel-like structure were synthesized, in which Gd congeners exhibited a significant magnetocaloric effect due to the high isotropy Gd nuclearity and weak ferromagnetic interactions. Abstract : Two novel wheel-like lanthanide nanoclusters with 42 nuclearity [Ln42 L14 (OH)28 (OAc)84 ] (abbreviated as Ln42 ; Ln = 1 -Gd, 2 -Dy ; HL = 3-methoxysalicylaldehyde O -vanillin) were structurally and magnetically characterized. The Ln42 species were constructed from O -vanillin and lanthanide acetate, in which a big cylindrical cavity formed with the external and internal diameters of the wheels in the clusters being about 3.6 nm and 1.5 nm, respectively. Both 1 -Gd and 2 -Dy exhibit high thermal stability and decompose above 320 °C. Strikingly, the Gd42 congener displayed significant magnetic refrigeration, the high isotropy Gd nuclearity and weak ferromagnetic interaction between adjacent Gd 3+ ions lead to a large magnetocaloric effect (MCE) with −Δ S m max = 42.60 J kg −1 K −1 .